PENGARUH GENDER CEO TERHADAP DATA BREACH RISK DENGAN IT GOVERNANCE SEBAGAI VARIABEL MEDIASI (Studi Empiris pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2021-2024) - Viola Cahya Maheswari; Wahyu Meiranto (Diponegoro Journal of Accounting, 2026)
This study aims to examine the effect of CEO Gender on data breach risk with IT Governance as a mediating variable in banking companies listed on the Indonesia Stock Exchange during the 2021–2024 period. The increasing incidence of data breaches in the Indonesian banking sector indicates that data breach mitigation is influenced not only by technological factors but also by decision-making characteristics at the top management level.This study employs a quantitative approach using secondary data from banking companies listed on the Indonesia Stock Exchange during 2021–2024. Data were analyzed using panel data regression with the Panel EGLS Cross-section Random Effects method, while mediation analysis was conducted using the Baron and Kenny procedure and the Sobel test.The results show that CEO Gender does not have a significant direct effect on data breach risk. However, IT Governance significantly mediates the relationship between CEO Gender and data breach risk. The mediation is classified as full mediation, indicating that the influence of CEO Gender on data breach risk operates through the IT Governance mechanism. These findings highlight the importance of strengthening IT Governance as a key strategy for mitigating data breach risk in the Indonesian banking sector.